Temporomandibular Joint Pain due to Osteochondroma of the Mandibular Condyle - Jerome A. Lindeboom; Jean Pierre T. F. Ho; Naomi Donner; Jan de Lange (Hindawi Limited, 2024)
Osteochondroma of the craniofacial region is rare. However, the most common site of osteochondroma in the craniofacial region is the mandibular coronoid process and mandibular condyle. Here, we report a case of a 32-year-old woman treated by condylectomy and secondary reconstruction with a temporomandibular joint prosthesis.